A PC-ABS automobile interior material containing glass fiber and preparation method thereof
By using the composite and glass fiber reinforcement of new and old ABS and PC materials in automotive interior materials, the problem of easy damage to existing materials under impact is solved, and higher machinery is achieved by reducing carbon emissions and improving environmental protection. Performance and environmentally friendly effects.
Patent Information
- Application Number
- CN202410261934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-03-07
AI Technical Summary
Existing ABS and PC composite materials are prone to damage or cracking due to impact in automotive interior applications, and their production process will emit a large amount of greenhouse gases such as carbon dioxide, affecting environmental protection.
PC-ABS automotive interior materials containing glass fiber are used, which are compounded from old and new ABS and PC materials with recycled ABS and PC materials, and glass fibers and compatibility agents are added to improve the strength and compatibility of the material.
Through the combination of new and old materials and glass fiber reinforcement, the mechanical properties and heat resistance of automotive interior materials are improved, carbon emissions are reduced, the environmental protection of the materials is enhanced, and the possibility of damage and cracking is reduced.
Smart Images

Figure GHA0000007977470000061 
Figure GHA0000007977470000081 
Figure GHA0000007977470000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of plastic alloys, and more specifically, to a PC-ABS automobile interior material containing glass fiber and a preparation method thereof. Background Art
[0002] ABS plastic is a ternary copolymer of acrylonitrile (A), butadiene (B), and styrene (S). The relative content of the three monomers can be changed arbitrarily to make various resins. ABS plastic has the common properties of the three components. A makes it resistant to chemical corrosion and heat, but its surface hardness is lower than that of PC. B makes it highly elastic and tough. S makes it have the processing and molding characteristics of thermoplastics and improves electrical properties. At the same time, ABS also has better processing fluidity. Therefore, ABS plastic has been widely used in manufacturing industries such as machinery, electrical, textile, automobile, aircraft, and shipbuilding, as well as chemical industry.
[0003] PC is polycarbonate, also known as PC plastic; it has the advantages of being colorless and transparent, heat-resistant, impact-resistant, flame-retardant BI grade, better wear resistance than ABS, and good mechanical properties, but it has high viscosity and is prone to stress cracking.
[0004] Therefore, ABS and PC are currently used in combination to combine their properties so that they can be used in the production of electronic product housings, automotive interior parts, etc. They have better mechanical properties and can reduce the damage and cracking of electronic product housings and automotive interior parts when they are hit. However, ABS and PC are mainly synthesized from petroleum raw materials, and a large amount of carbon dioxide, carbon monoxide and other substances will be emitted during their production process, which will increase carbon emissions, reduce their environmental friendliness, cause certain damage to the atmosphere, and at the same time aggravate the trend of global warming.
[0005] In order to reduce carbon emissions and reduce the impact on the environment, there is currently a method of compounding recycled ABS and recycled PC to reduce carbon emissions and be more environmentally friendly. However, the impurity content in recycled ABS and PC materials is high and the performance is unstable; and the toughness and strength of the compounded recycled ABS and recycled PC composite materials are lower than those of ABS and PC composite materials. Therefore, when used in automotive interior parts, when subjected to force or impact, they are prone to breakage and cracking, thereby reducing their practicality, so further research is needed. Summary of the invention
[0006] In order to reduce carbon emissions and obtain better mechanical properties, the present application provides a PC-ABS automotive interior material containing glass fiber and a preparation method thereof.
[0007] In a first aspect, the present application provides a PC-ABS automotive interior material containing glass fiber, which is composed of the following raw materials in parts by weight:
[0008] ABS: 10-20 copies
[0009] PC: 5-8 copies
[0010] Recycled ABS: 30-40 pieces
[0011] Recycled PC: 10-20 pieces
[0012] Glass fiber: 20-40 parts
[0013] Compatibilizer: 5-10 parts
[0014] Other additives: 3-5 parts;
[0015] The compatibilizer is one or more of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer.
[0016] The above raw material composition and raw material dosage are the preferred ranges of this application. By utilizing new ABS and PC materials and blending them with recycled ABS and recycled ABS, the new and the old are combined to comprehensively improve their performance. At the same time, it can reduce carbon emissions and improve its environmental friendliness.
[0017] Adding glass fiber, which is the abbreviation of glass fiber, has the advantages of good insulation, strong heat resistance, good corrosion resistance, and high mechanical strength. Adding glass fiber can further improve the strength and heat resistance of PC-ABS automotive interior materials.
[0018] Compatibilizers can promote the mixing and compatibility of various raw materials to enhance the interfacial adhesion of the raw material system, thereby further improving the comprehensive performance of PC-ABS automotive interior materials.
[0019] Maleic anhydride grafted POE has elasticity, compatibility, etc.
[0020] Maleic anhydride grafted EAA has better environmental stress cracking, compatibility and toughness, and ethylene-butyl acrylate-glycidyl methacrylate copolymer has better compatibility and toughening effect. Therefore, using one or more of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer as a compatibilizer has better compatibility and toughening effect, so it can further improve the mechanical properties of PC-ABS automotive interior materials and reduce the possibility of cracking and breakage due to impact.
[0021] In summary, the recycled ABS and recycled ABS added in this application can reduce carbon emissions, making it green and environmentally friendly, and then compounding with ABS and PC to obtain better comprehensive performance. By adding one or more compatibilizers composed of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-methacrylate glycidyl ester copolymer, the compatibility of its raw material system is further improved, making its raw material system structure tight. Then, through the reinforcement of glass fiber, the PC-ABS automotive interior material has better strength, and with the auxiliary effect of other additives, the obtained PC-ABS automotive interior material has better physical properties. Therefore, the produced automotive interior is not prone to damage, cracking, etc. when impacted, which improves its practicality.
[0022] Automobile interior parts generally refer to the car compartment partitions, door trim panels, dashboard assemblies, armrests, carpets and other parts and materials. The above interior parts are only some auxiliary parts, but they have to bear the functions of vibration reduction, heat insulation, sound absorption and sound insulation, and play a very important role in the comfort of the car. Some interior parts require a certain hardness of the material, and are not easy to deform when subjected to force, and are not easy to be damaged or cracked when impacted. Therefore, during emergency braking, due to inertia, it is inevitable that some items in the car will hit the car interior parts due to inertia. Such as the door handles and side walls inside the car.
[0023] The PC-ABS automotive interior material produced by the present application can reduce the possibility of damage and cracking when hit, thereby improving the durability of PC-ABS automotive interior parts.
[0024] Preferably, the weight ratio of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer is (3-5):(1-3):1.
[0025] When maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer are compounded, a synergistic effect is achieved to further improve the comprehensive performance of PC-ABS automotive interior materials, further reduce the possibility of damage and cracking of automotive interior parts when they are impacted, and at the same time, when automotive interior parts are subjected to stress, they are not easily deformed.
[0026] Preferably, the glass fiber has a length of 20-30 μm and a wire diameter of 3-8 μm.
[0027] The above glass fiber length and wire diameter range can be easily mixed with the raw material system of PC-ABS automotive interior materials, so that the raw material system is closely combined, further improving the mechanical strength of PC-ABS automotive interior materials and reducing the possibility of breakage and cracking.
[0028] Preferably, the glass fiber is a modified glass fiber, and the modified glass fiber is composed of the following raw materials in parts by weight:
[0029] Glass fiber 80-100 parts
[0030] Acrylic acid 1-3 parts
[0031] Epoxy soybean oil acrylate 1-5 parts
[0032] 3-8 parts of hydrogen furfuryl methacrylate
[0033] 1-3 parts triisopropylsilyl methacrylate
[0034] Diallyl maleate 0.5-1.5 parts
[0035] Initiator 0.1-0.5 parts
[0036] 10-20 parts of solvent.
[0037] Preferably, the modified glass fiber is prepared by the following method:
[0038] According to parts by weight, acrylic acid, epoxy soybean oil acrylate, furfuryl methacrylate, triisopropylsilyl methacrylate, diallyl maleate, an initiator and 2 / 1 solvent are weighed and mixed evenly, heated to 60-70° C., reacted for 1-3 hours to obtain a copolymer, and then 1 / 2 of the solvent is added to mix with the copolymer, and stirred at a rotation speed of 300-500 r / min for 20-30 minutes to obtain a copolymer emulsion; then glass fiber is added to the copolymer emulsion and mixed evenly to obtain a blend, the blend is heated to 105-115° C., vacuum distilled to remove the solvent, and solidified to obtain a modified glass fiber.
[0039] Epoxidized soybean oil acrylate is prepared by the ring-opening reaction of acrylic acid and soybean oil. Therefore, it has the characteristics of acrylic acid and epoxy soybean oil, and has the advantages of low viscosity, good wettability, etc. Furfuryl methacrylate is a polymerization monomer, diallyl maleate is a reaction intermediate, triisopropylsilyl methacrylate is a functional acrylate monomer, and can improve the compatibility of glass fiber with organic matter. Therefore, the present application is compounded by acrylic acid, epoxy soybean oil acrylate, furfuryl methacrylate, triisopropylsilyl methacrylate, and diallyl maleate, and reacts to form a macromolecular complex under the action of an initiator.
[0040] Through the dilution effect of the solvent and high-speed stirring, a polymer emulsion is formed. The polymer emulsion has good film-forming properties, good wettability and good compatibility, so it is easy to wet and disperse the glass fiber, and after solidification, the surface of the glass fiber is coated. After solidification and removal of the solvent, a coating film is formed on the surface of the glass fiber. Therefore, the obtained modified glass fiber is easy to mix with the PC-ABS automotive interior material raw material system, so that the PC-ABS automotive interior material has better mechanical properties. Therefore, the produced automotive interior parts are not easy to be damaged or cracked when impacted.
[0041] Preferably, the initiator is one or more of tert-butyl perbenzoate, azobisisobutyronitrile, and dibenzoyl peroxide.
[0042] The above initiators can promote the composite copolymerization reaction of reactive monomers such as acrylic acid, furfuryl methacrylate, triisopropylsilyl methacrylate, etc., and the copolymer emulsion formed by cooperating with other raw materials is easy to adhere to the surface of glass fiber, and after removing the solvent and curing, the formed coating film is stably coated on the glass fiber, and the coating film has good compatibility with the raw material system of PC-ABS automotive interior materials, so that the PC-ABS automotive interior materials have better mechanical properties.
[0043] Preferably, the other auxiliary agent is an anti-aging agent and / or a wetting agent.
[0044] By adding anti-aging agents, the anti-aging properties of PC-ABS automotive interior materials can be improved, reducing the possibility of aging and performance degradation. Wetting agents can further promote the processing of the raw material system of PC-ABS automotive interior materials and improve processing efficiency.
[0045] Preferably, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168.
[0046] The above antioxidants all play a good antioxidant role, reducing the possibility of aging and other degradation of physical properties after the use of PC-ABS automotive interior materials.
[0047] Preferably, the lubricant is one or more of polyethylene wax, PETS, EBS, and triphenyl phosphate.
[0048] The above wetting agents all play a lubricating role and improve the convenience of processing.
[0049] In a second aspect, the present application provides a method for preparing a PC-ABS automobile interior material containing glass fiber, comprising the following steps:
[0050] ABS, PC, recycled ABS, recycled PC, glass fiber, compatibilizer and other additives are weighed and mixed evenly according to weight parts, and then extruded and granulated to obtain automobile interior materials.
[0051] The PC-ABS automotive interior material prepared by the above method can not only reduce carbon emissions and be green and environmentally friendly, but also enable the PC-ABS automotive interior material to obtain better physical properties. The resulting automotive interior material is less likely to be damaged or cracked when impacted, thereby improving its practicality.
[0052] In summary, this application has the following beneficial effects:
[0053] 1. The recycled ABS and recycled ABS added in this application can reduce carbon emissions and make it green and environmentally friendly, and then compound with ABS and PC to obtain better comprehensive performance. Then, by adding one or more compatibilizers composed of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer, the compatibility of its raw material system is further improved, making its raw material system structure compact.
[0054] The PC-ABS automotive interior material has better strength through the reinforcement of glass fiber, and with the assistance of other additives, the PC-ABS automotive interior material has better physical properties. Therefore, the automotive interior produced is not easy to be damaged or cracked when impacted, which improves its practicality.
[0055] 2. The present application is compounded by acrylic acid, epoxy soybean oil acrylate, furfuryl methacrylate, triisopropylsilyl methacrylate, and diallyl maleate, and reacts to form a macromolecular complex under the action of an initiator.
[0056] Through the dilution effect of the solvent and high-speed stirring, a polymer emulsion is formed. The polymer emulsion has good film-forming properties, good wettability and good compatibility, so it is easy to wet and disperse the glass fiber, and after solidification, the surface of the glass fiber is coated. After solidification and removal of the solvent, a coating film is formed on the surface of the glass fiber. Therefore, the obtained modified glass fiber is easy to mix with the PC-ABS automotive interior material raw material system, so that the PC-ABS automotive interior material has better mechanical properties. Therefore, the produced automotive interior parts are not easy to be damaged or cracked when impacted. DETAILED DESCRIPTION
[0057] The present application is further described in detail below with reference to the embodiments.
[0058] The sources or performance parameters of some raw materials;
[0059] Table 1 Sources or performance parameters of some raw materials
[0060]
[0061]
[0062] Preparation example of modified glass fiber
[0063] Preparation Example 1
[0064] The modified glass fiber is prepared by the following method:
[0065] 1kg of acrylic acid, 1kg of epoxy soybean oil acrylate, 3kg of furfuryl methacrylate, 1kg of triisopropylsilyl methacrylate, 0.5kg of diallyl maleate, 0.1kg of tert-butyl perbenzoate and 5kg of ethyl acetate were weighed and put into a reactor and mixed evenly, heated to 60°C, reacted for 3h to obtain a copolymer, 5kg of ethyl acetate was added and mixed with the copolymer, and stirred at a speed of 300r / min for 20min to obtain a copolymer emulsion; glass fiber at 80°C was added and mixed evenly with the copolymer emulsion to obtain a blend, the blend was heated to 105°C, and reduced pressure distillation was started with a vacuum gauge of -0.1Mpa to remove ethyl acetate, and solidified to obtain a modified glass fiber.
[0066] Preparation Example 2
[0067] The modified glass fiber is prepared by the following method:
[0068] Weigh 2kg of acrylic acid, 3kg of epoxy soybean oil acrylate, 5kg of furfuryl methacrylate, 2kg of triisopropylsilyl methacrylate, 1kg of diallyl maleate, 0.1kg of tert-butyl perbenzoate, 0.1kg of azobisisobutyronitrile and 8kg of ethyl acetate, put them into a reactor and mix them evenly, heat them to 60°C, react for 3h to obtain a copolymer, then add 8kg of ethyl acetate and mix them with the copolymer, stir them at a speed of 300r / min for 20min to obtain a copolymer emulsion; then add 80kg of glass fiber and mix them evenly with the copolymer emulsion to obtain a blend, heat the blend to 110°C, start reduced pressure distillation, the vacuum meter shows -0.1Mpa, remove the ethyl acetate, and solidify it to obtain a modified glass fiber.
[0069] Preparation Example 3
[0070] The modified glass fiber is prepared by the following method:
[0071] Weigh 3kg of acrylic acid, 5kg of epoxy soybean oil acrylate, 8kg of furfuryl methacrylate, 3kg of triisopropylsilyl methacrylate, 1kg of diallyl maleate, 0.1kg of tert-butyl perbenzoate, 0.1kg of azobisisobutyronitrile, 0.1kg of dibenzoyl peroxide and 10kg of ethyl acetate, put them into a reactor and mix them evenly, heat them to 60°C, react for 3h to obtain a copolymer, then add 20kg of ethyl acetate and mix them with the copolymer, stir them at a speed of 300r / min for 20min to obtain a copolymer emulsion; then add 8kg of glass fiber and mix them evenly with the copolymer emulsion to obtain a blend, heat the blend to 115°C, start reduced pressure distillation, the vacuum meter shows -0.1Mpa, remove the ethyl acetate, and solidify it to obtain a modified glass fiber.
[0072] Preparation Comparative Example
[0073] Preparation Comparative Example 1
[0074] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of furfuryl methacrylate is replaced by epoxidized soybean oil acrylate.
[0075] Preparation Comparative Example 2
[0076] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that triisopropylsilyl methacrylate is replaced by hydrogen furfuryl methacrylate in an equal amount.
[0077] Preparation Comparative Example 3
[0078] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of diallyl maleate is replaced by furfuryl methacrylate.
[0079] Preparation Comparative Example 4
[0080] The difference between the comparative example 4 and the preparation example 1 is that an equal amount of epoxidized soybean oil acrylate and hydrogen furfuryl methacrylate are used.
[0081] Preparation Comparative Example 5
[0082] The difference between Preparation Comparative Example 5 and Preparation Example 1 is that triisopropylsilyl methacrylate and diallyl maleate are replaced by hydrogen furfuryl methacrylate in equal amounts.
[0083] Example
[0084] Example 1
[0085] A method for preparing a glass fiber-containing PC-ABS automobile interior material comprises the following steps:
[0086] Weigh ABS, PC, recycled ABS, recycled PC, glass fiber, compatibilizer, and other additives and put them into a high-speed mixer. Stir for 10 minutes at a speed of 300 r / min to mix the materials evenly. Then transfer them to a twin-screw extruder for melting and extrusion at a screw speed of 400 rpm. Cool them in a cold water tank, dry them in an oven at 120°C for 10 seconds, and then transfer them to a granulator for granulation to obtain automotive interior materials.
[0087] The temperature settings of the twin-screw extruder are as follows: zone 1 220°C, zone 2 235°C, zone 3 250°C, zone 4 255°C, zone 5 260°C, zone 6 240°C, zone 7 235°C, and die head 230°C.
[0088] Embodiment 2-9
[0089] The difference between Example 2-9 and Example 1 is that the amount of raw materials used is different, as shown in Table 2, wherein the wire diameter of the glass fiber is represented by and the length is represented by L;
[0090] Table 2 Raw material dosage of Examples 1-9 (kg)
[0091]
[0092]
[0093] Examples 10-17
[0094] The difference between Examples 10-18 and Example 8 is that the glass fibers used are modified glass fibers, and the sources of the modified glass fibers of Examples 10-18 are different, as shown in Table 3.
[0095] Table 3 Sources of modified glass fibers of Examples 10-17
[0096]
[0097]
[0098] Comparative Example
[0099] Comparative Example 1
[0100] The difference between Comparative Example 1 and Example 1 is that BS is replaced by recycled ABS, and PC is replaced by recycled PC.
[0101] Comparative Example 2
[0102] The difference between Comparative Example 2 and Example 1 is that the recycled ABS is replaced by ABS, and the recycled PC is replaced by PC.
[0103] Comparative Example 3
[0104] The difference between Comparative Example 3 and Example 1 is that the amount of the acrylate and glycidyl ester difunctional ethylene elastomer used is 1 kg.
[0105] Comparative Example 4
[0106] The difference between Comparative Example 4 and Example 1 is that the amount of the acrylate and glycidyl ester difunctional ethylene elastomer used is 15 kg.
[0107] Comparative Example 5
[0108] The difference between Comparative Example 5 and Example 1 is that the glass fibers are replaced by carbon fibers (with a length of 20 μm and a wire diameter of 3 μm) in equal amounts.
[0109] Comparative Example 6
[0110] The difference between Comparative Example 6 and Example 1 is that the glass fiber is replaced by 300 mesh silica in equal amount.
[0111] Performance testing
[0112] The ABS modified materials obtained in Examples 1-17 and Comparative Examples 1-6 were injection molded, and the obtained test samples were used for the following test. The specific data are shown in Table 4.
[0113] Detection method / test method
[0114] Test method: Tensile strength: refer to ASTM D638, the test condition is 50mm / min, the thickness of the test sample is 2mm.
[0115] Elongation at break: refer to ASTM D638, the test condition is 50mm / min, the thickness of the test sample is 2mm.
[0116] Izod notched impact strength: carried out in accordance with ASTM D256, the test conditions are 2mm V-notch, temperature is 25°C, and the thickness of the test sample is 3.2mm.
[0117] The above data were tested 3 times and the average value was taken. The specific data are shown in Table 4;
[0118] Table 4 Experimental data of Examples 1-17 and Comparative Examples 1-6
[0119]
[0120]
[0121] The following test phases were evaluated in conjunction with Table 4:
[0122] By comparing Example 1 with Comparative Example 1, it can be seen that the tensile strength, elongation at break and impact strength of Example 1 are higher than those of Comparative Example 1, indicating that compounding of new and old ABS and PC can not only reduce carbon emissions but also be green and environmentally friendly, so that the PC-ABS automotive interior material obtains better mechanical properties and reduces the possibility of breakage and cracking.
[0123] By comparing Example 1 and Example 2, it can be seen that the tensile strength, elongation at break and impact strength of Example 2 are slightly greater than those of Example 1, but Example 1 does not use recycled materials. In comparison, Example 1 is more environmentally friendly.
[0124] By comparing Example 1 with Comparative Examples 3-4, it can be seen that the impact strength of Example 1 is higher than that of Comparative Examples 3-4, indicating that the PC-ABS automotive interior material with better impact strength can be obtained by using the compatibilizer dosage range of the present application.
[0125] By comparing Example 1 with Comparative Examples 5-6, it can be seen that the tensile strength and impact strength of Example 1 are higher than those of Comparative Examples 5-6, indicating that the present application adopts glass fiber to obtain PC-ABS automotive interior materials with better mechanical properties.
[0126] By comparing Example 2 with Examples 7-9, it can be seen that the tensile strength, elongation at break and impact strength of Example 2 are higher than those of Examples 7-9, indicating that after compounding with maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer, the mechanical properties of the PC-ABS automotive interior material are better, reducing the possibility of breakage and cracking.
[0127] By comparing Example 8 and Example 10, it can be seen that the tensile strength, elongation at break and impact strength of Examples 7-9 are higher than those of Example 1, indicating that the use of modified glass fiber can improve the mechanical properties of PC-ABS automotive interior materials and reduce the occurrence of breakage, cracking and the like.
[0128] By comparing Example 10 with Examples 13-17, it can be seen that the tensile strength, elongation at break and impact strength of Example 10 are higher than those of Examples 13-17, indicating that the modified glass fiber obtained by compounding with oxysoybean oil acrylate, furfuryl methacrylate, triisopropylsilyl methacrylate and diallyl maleate and reacting under the action of an initiator to form a macromolecular complex used to coat the glass fiber has better mechanical properties.
[0129] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A PC-ABS automobile interior material containing glass fiber, characterized in that: It is composed of the following raw materials in parts by weight: ABS: 10-20 copies PC: 5-8 copies Recycled ABS: 30-40 pieces Recycled PC: 10-20 pieces Modified glass fiber: 20-40 parts Compatibilizer: 5-10 parts Other additives: 3-5 parts; The compatibilizer is one or more of maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer; The modified glass fiber is composed of the following raw materials in parts by weight: Glass fiber 80-100 parts Acrylic acid 1-3 parts Epoxy soybean oil acrylate 1-5 parts 3-8 parts of hydrogen furfuryl methacrylate 1-3 parts triisopropylsilyl methacrylate Diallyl maleate 0.5-1.5 parts Initiator 0.1-0.5 parts 10-20 parts of solvent; The modified glass fiber is prepared by the following method: According to parts by weight, acrylic acid, epoxy soybean oil acrylate, furfuryl methacrylate, triisopropylsilyl methacrylate, diallyl maleate, an initiator and 1 / 2 of a solvent are weighed and mixed evenly, heated to 60-70° C., reacted for 1-3 hours to obtain a copolymer, 1 / 2 of the solvent is added to mix with the copolymer, stirred at a speed of 300-500 r / min for 20-30 minutes to obtain a copolymer emulsion; glass fiber is added to mix with the copolymer emulsion evenly to obtain a blend, the blend is heated to 105-115° C., vacuum distilled to remove the solvent, and solidified to obtain a modified glass fiber.
2. The glass fiber-containing PC-ABS automotive interior material according to claim 1, characterized in that: The weight ratio of the maleic anhydride grafted POE, maleic anhydride grafted EAA, and ethylene-butyl acrylate-glycidyl methacrylate copolymer is (3-5): (1-3):
1.
3. The glass fiber-containing PC-ABS automotive interior material according to claim 1, characterized in that: The glass fiber has a length of 20-30 μm and a wire diameter of 3-8 μm.
4. The glass fiber-containing PC-ABS automotive interior material according to claim 1, characterized in that: The initiator is one or more of tert-butyl perbenzoate, azobisisobutyronitrile and dibenzoyl peroxide.
5. The glass fiber-containing PC-ABS automotive interior material according to claim 1, characterized in that: The other auxiliary agents are antioxidants and / or lubricants.
6. The glass fiber-containing PC-ABS automotive interior material according to claim 5, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 168.
7. The glass fiber-containing PC-ABS automotive interior material according to claim 5, characterized in that: The lubricant is one or more of polyethylene wax, PETS, EBS and triphenyl phosphate.
8. A method for preparing a glass fiber-containing PC-ABS automobile interior material according to any one of claims 1 to 7, characterized in that: The following steps are involved: ABS, PC, recycled ABS, recycled PC, modified glass fiber, compatibilizer and other additives are weighed and mixed evenly according to weight parts, and then extruded and granulated to obtain automobile interior materials.
Citation Information
Patent Citations
Lightweight PC-ABS flame-retardant composite material and preparation method thereof
CN117447828A